Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Produktivitas di Industri Kreatif - Anggun Okta Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to investigate the relationship between job satisfaction, motivation, skill development, and employee productivity in five creative companies in Bandung. The sample consisted of 100 employees who completed a questionnaire covering these key variables. Quantitative analysis used descriptive statistics to describe the means and standard deviations of the variables, as well as inferential statistics including correlation tests and regression analysis to explore the relationships between variables. Results show that high levels of job satisfaction, motivation, and continuous skills development are positively and significantly correlated with increased employee productivity. The managerial implications of these findings suggest the importance of effective human resource management strategies to improve organizational performance and maintain competitiveness in the creative industry. Future research could explore additional factors that influence productivity, as well as examine the impact of management interventions to improve positive working conditions for employees